Azide‐substituted Poly(N‐ethyl‐3‐vinylcarbazole) as a Thermally Cross‐Linkable Hole‐Transporting Material for Polymeric Light‐Emitting Diodes. Issue 1 (2nd August 2017) - Leung, Man‐kit; Chang, Chiou‐Ling; Chang, Chung‐Yi; Chuang, Ching‐Nan; Lin, Che‐Tseng
Abstract : We have successfully synthesized a series of thermally cross‐linkable azide‐substituted poly( N ‐ethyl‐3‐vinylcarbazoles)P1–P6 . These polymers can be self‐cross‐linked by heat treatment under atmospheric conditions to form insoluble polymer matrices. Their electronic properties can be tuned by using various triphenylamine‐substituted alkyne‐based curing agents as additives. The polymeric materials can be simply coated on a substrate by spin coating or dip coating. Through the Huisgen 1, 3‐dipolar cycloaddition reaction, the polymeric film can be cured by alkyne‐based curing agents effectively under copper‐free conditions. This approach can be utilized in the fabrication of multilayer polymeric light‐emitting devices (PLEDs). Under optimized conditions, we have demonstrated that the PLED of ITO/curedP5 /PVK‐Ir(ppy)3 ‐ t ‐PBD/Mg–Ag shows a turn‐on voltage of 10.1 V (1 cd/m 2 ), with the maximum brightness of 7851 cd/m 2 and current efficiency of 12.8 cd/A. Abstract : The Huisgen reaction‐cured hole‐transport layer (HTL) shows good solvent resistance. This material provides a useful option for the fabrication of multilayer devices through solution processing. For example, under the optimized conditions, a polymeric light‐emitting device that was fabricated by this approach showed a turn‐on voltage of 10.1 V (1 cd/m 2 ), maximum brightness of 7851 cd/m 2, and current efficiency of 12.8 cd/A.